Prevalence of depression in junior and senior adolescents - Zhang, Jing; Liu, Dehuan; Ding, Linwei; Du, Guankui (Frontiers in Psychiatry, 2023)
Background Depression affects the development of adolescents and makes it difficult for them to adapt to future life. The purpose of this study was to elucidate the population characteristics of adolescent depression. Methods This study measured depression based on the Patient Health Questionnaire-9 items and sociodemographic questionnaire. A total of 8,235 valid questionnaires were collected from six schools in Haikou and Qionghai, Hainan Province, covering the ages of 13 to 18. The questionnaires included high schools with multiple levels, including general high schools, key high schools, and vocational high schools. Latent category analysis (LCA) was used to identify potential categories of depressive symptoms among adolescents. Latent Class Analysis (LCA) was used for determining depressive symptom latent categories and their proportional distribution among adolescents. Results LCA analysis divided the data into 3 categories, namely no depression, low depression, and high depression groups. The percentage of the high depression group was 10.1%, and that of the low depression group was 48.4%. The Jorden index was greatest for a PHQ-9 score of 14.5. The 1st grade of junior middle school students entered the high and low depression groups 1.72 and 1.33 times more often than seniors. The number of the 1st grade of high school students included in the high and low depression groups was 1.55 and 1.42 times of the 3rd grade of high school students group. The detection rate of the high depression group of vocational school adolescents was 13.5%, which was significantly higher than that of key high schools (9.6%) and general high schools (9.0%). Conclusion This study found that 1st grade of junior middle school students and the 1st grade of high school students were more likely to fall into depressive conditions. Moreover, Adolescent girls require more attention than boys. Vocational school students need more psychological guidance.